2016
DOI: 10.5966/sctm.2015-0347
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Mesenchymal Stem Cell Therapy Promotes Osteoblastogenesis and Prevents Glucocorticoid-Induced Osteoporosis

Abstract: Gene-modified mesenchymal stem cell (MSC)-like cells with enhanced bone marrow homing and osteogenesis have been used in treating glucocorticoid-induced murine osteoporosis (GIOP). Recent preclinical studies have further demonstrated the immunomodulatory and anticatabolic potential of allogeneic MSCs in treating osteoporosis under inflammatory and autoimmune conditions. In this study, we investigated whether systemic infusion of allogeneic MSCs without genetic manipulation could prevent GIOP, whether anabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(105 citation statements)
references
References 29 publications
3
102
0
Order By: Relevance
“…S2A-D), and were in accordance with surface profiles currently recognized to represent MSCs (Fig. S2E) 8, 23, 42. MSCs were infused at D25, at which time point hyperglycemia in T1D mice was stable around 400 mg/dL, as shown previously 25 and here by 3 consecutive quantifications (Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…S2A-D), and were in accordance with surface profiles currently recognized to represent MSCs (Fig. S2E) 8, 23, 42. MSCs were infused at D25, at which time point hyperglycemia in T1D mice was stable around 400 mg/dL, as shown previously 25 and here by 3 consecutive quantifications (Fig.…”
Section: Resultssupporting
confidence: 86%
“…According to reported data, systemically transplanted MSCs rescue bone loss through either circulatory immunomodulation/anti-inflammation 7 or local effects via homing to recipient bone marrow post infusion 8, 9. In this study, we confirmed that infused MSCs existed in recipient circulation for less than 24 h by using MSCs from GFP-transgenic donor mice (Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Immunofluorescent staining was performed according to our previous work (Sui et al ., 2016b). Specimens were fixed overnight with 4% paraformaldehyde, cryoprotected with 30% sucrose, embedded in the optimal cutting temperature compound, snap‐frozen, and sectioned into 15‐μm sagittal sections (CM1950, Leica, Solms, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacokinetic studies have indicated that ~50% of the alendronate absorbed into the body binds to bone surface, while the other 50% is rapidly excreted from the kidneys (20,23,24). Besides conventional chemical therapy, stem cell therapy has been demonstrated to lead to an improvement in patients with osteoporosis by promoting osteo-in patients with osteoporosis by promoting osteo-by promoting osteogenesis and preventing the progression of osteoporosis (25,26). We previously isolated a population of multipotent cells from a human full-term placenta, termed placenta-derived multipotent cells (PDMCs), which were able to differentiate into a range of cell types, including cells with an osteoblastic phenotype (27).…”
Section: Introductionmentioning
confidence: 99%